Social-Demographic Characteristics of Acceptance of Measles Rubella Immunization in Tongkuno District, Indonesia - Yanna Mellina; Arifin Seweng; Andi Mardiah Tahir (Humanistic Network for Science and Technology (HNST), 2019)
Acceptance of immunization is one of the challenges faced by the government in the Rubella Measles immunization program. This study aims to measure the influence of social demography on the acceptance of Measles Rubella immunization in Tongkuno District, Indonesia. The study was conducted in the working area of Tongkuno Health Center, Muna Regency. The research design used was a cross sectional study. The research sample was 299 people who were selected using the proportional stratified random sampling technique. Data were analyzed using chi square test and logistic regression. The results showed the socio-demographic characteristics associated with receipt of Tongkuno District rubella measles immunization were the age of the child (p-value = 0.008), children's education (p-value = 0.002) and age of parents (p-value = 0.015). Child education is the variable most associated with the acceptance of MR immunization with an OR value of 0.155 (95% CI: 0.045 - 0.539). The intensive socialization of MR immunization carried out by the government in all circles makes it easy for people to receive information that is not only influenced by education and the work of parents. counseling needs to be done and periodic outreach to both the community and mothers who have children about the benefits of MR immunization. Keywords: Socio-demographic characteristics; immunization; measles; rubella; tongkuno; Indonesia